Isolasi dan Karakterisasi Parsial Bakteri Indigenous Pemfermentasi dari Buah Durian (Durio zibethinus Murr.) - Azizah Nurmalinda; - Periadnadi; - Nurmiati (Jurnal Biologi Universitas Andalas, 2013)
The research related to the isolation and partial characterization of indigenous fermenting bacteria from durian fruit (Durio zibethinus Murr.) was conducted from May to August 2012 in Laboratory of Microbiology, Biology Department, Andalas University. Experimental method was used and was descriptively analyzed. Ripe durian fruit contain indigenous fermenting as well as nonfermenting bacteria, that was recognized from halozone around the colony on modified GTA medium. Indigenous fermenting bacterias on the flesh of durian fruit have been characterized as Gram-positive, bacil, no endospores, motile and catalase positive. These isolates are proteolytics, amylolytics and cellulolytics and have no ability to hydrolyze fats and alcohol.Keywords : durian, fermenting, indigenous bacteria